Removal of pharmaceuticals from water with MXene hybrid materials - Hentula, Roni (My University, 2024)
Water is essential to everyday life and is one of the most important resources in the world. Among the vast number of pollutants, pharmaceuticals constitute a major share. In this work, we have studied the adsorption of two main pharmaceutical drugs diclofenac and paracetamol onto MXene based hybrid materials. Majority of these pharmaceuticals end up being part of the water bodies causing harm to aquatic life and other wildlife. Current methods for addressing this issue are costly and not accessible to everyone. MXene based materials may hold potential in addressing this problem. MXenes are novel 2D-materials that were discovered in 2011. They have a structure of Mn+1XnTx, where M is an early transition metal, X is either carbon or nitrogen, and T represents the surface terminating groups. In this work, the MAX precursor used was Ti3AlC2 and through the etching process, Al was eliminated, resulting in MXene Ti3C2Tx. MXenes have garnered significant attention in recent years due to their remarkable properties. One major challenge that needed to be addressed was the development of water-resistant materials. Typically, MXene films delaminate in water, making the use of pure MXene films unfeasible in water purification applications. The goal of this work was to produce MXene hybrid materials capable of removing pharmaceuticals from water. Five different combinations were evaluated to determine the optimal hybrid material for pharmaceutical removal. The best combination was found to be MXene: PVA: TMPyP (MPP) 8:2:1. This hybrid film was successful in removing diclofenac from the water solution. The film’s pharmaceutical removal properties were tested in three different conditions: ambient conditions, under a halogen lamp, and in the dark. The best results were obtained under halogen lamp, which may be due to the photocatalytic property of porphyrin. The removal of pharmaceuticals was monitored using UV-Vis. MPP hybrid films properties were examined using several techniques. The interlayer spacing increased according to XRD and SEM results. Further information about the chemical composition was provided by FTIR and Raman spectroscopy, which revealed that MXene’s primary functional group is -O(OH). Additionally, the issue of MXene film delamination was effectively resolved with the use of this water-resistant MPP hybrid material.
Keywords: MXenes, hybrid materials, diclofenac, water purification, Ti3AlC2